2014
DOI: 10.1016/j.ejmhg.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Study of toll-like receptor 7 expression and interferon α in Egyptian patients with chronic hepatitis C Infection and Hepatocellular Carcinoma

Abstract: Background: Hepatitis C virus is considered to be one of the most important devastating causes of chronic hepatitis, cirrhosis, and hepatic cellular carcinoma. Toll-like receptor 7 (TLR7) is a pathogen-recognition receptor that is expressed on innate immune cells. It recognizes viral RNA which induces its activation with a subsequent increase in IFN-a transcription. It has been postulated that HCV may cause down regulation of these receptors as one of immune evading mechanisms that participate in viral persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Also, Sato et al reported that the expression level of TLR4, TLR7 and TLR8 in CD14 + monocytes of Peripheral Blood Mononuclear Cells (PBMCs), from HCV-infected patients, significantly increased compared to those of controls, while the expression levels of the other TLRs were similar between the patients and the controls ( 20 ). In contradiction to these results, Abdel-Raouf et al showed that there was a highly significant decrease in TLR7 mRNA expression in PBMCs of HCV-infected subjects compared to the control group and in hepatocellular carcinoma group ( 21 ). These findings of Abdel-Raouf et al were in agreement with the results of Atencia et al, which found a significant down regulation in TLR3 and TLR7 mRNA levels in chronic HCV infection with cirrhosis compared to healthy controls ( 14 ).…”
Section: Discussionmentioning
confidence: 89%
“…Also, Sato et al reported that the expression level of TLR4, TLR7 and TLR8 in CD14 + monocytes of Peripheral Blood Mononuclear Cells (PBMCs), from HCV-infected patients, significantly increased compared to those of controls, while the expression levels of the other TLRs were similar between the patients and the controls ( 20 ). In contradiction to these results, Abdel-Raouf et al showed that there was a highly significant decrease in TLR7 mRNA expression in PBMCs of HCV-infected subjects compared to the control group and in hepatocellular carcinoma group ( 21 ). These findings of Abdel-Raouf et al were in agreement with the results of Atencia et al, which found a significant down regulation in TLR3 and TLR7 mRNA levels in chronic HCV infection with cirrhosis compared to healthy controls ( 14 ).…”
Section: Discussionmentioning
confidence: 89%
“…To explore the potential mechanisms by which Imiquimod suppresses CSC numbers, it was hypothesized that Imiquimod inhibited malignant cellular behaviors in HCC cells and HCC stem cells through downregulation of IKK-NFκB-IL6 signaling, which had previously been demonstrated to function in TLR7-dominated hepatic diseases ( 8 , 9 , 19 ). The expression levels of IKK, NFκB and IL6 were all significantly decreased in the Imiquimod-treated group (P<0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the potential capacity of the vRNA of different influenza strains to stimulate TLRs 7 and 8 was found to be correlated to the virulence of the strains [ 141 ]. In addition, SNPs in the TLR7 and TLR8 genes were associated with the CD4 T cell count during an HIV infection [ 142 ] as well as the levels of type 1 IFN and proinflammatory cytokines and the progression to hepatocellular carcinoma during an HCV infection [ 143 , 144 ]. Also, the low copy numbers of the TLR7 gene is associated with the establishment of chronic HBV infection [ 145 ].…”
Section: Tlrs 7 and 8 And The Pathogenesis Of Viral Infectionsmentioning
confidence: 99%